Integrasi Ilmu Agama dan Sains: Paradigma Transformasi Kurikulum Pesantren di Era Global - M. Dihram; Said Masykur (ALSYS, 2026)
The transformation of the pesantren curriculum is an important need in responding to global challenges and the development of science, particularly in efforts to overcome the dichotomy between religious knowledge and science. However, studies that specifically discuss the integration of religious knowledge and science in the context of pesantren curriculum transformation remain limited. This study aims to analyze the forms of integration between religious knowledge and science in the pesantren curriculum as an educational model that is relevant to contemporary developments and the improvement of educational quality. This study uses a qualitative approach with a library research method. Data were obtained through a review of books, scholarly articles, and relevant documents discussing knowledge integration and pesantren curriculum transformation, then analyzed using content analysis techniques to identify the concepts, challenges, and prospects for developing an integrative curriculum. The results of the review show that the integration of religious knowledge and science is a relevant paradigm for overcoming the dichotomy of knowledge while also serving as the basis for transforming the pesantren curriculum to be adaptive to the dynamics of contemporary education. This transformation can be realized through curriculum integration, the application of integrative learning methods, the development of interdisciplinary modules, and the strengthening of Islamic values in the use of technology. These findings reaffirm the role of pesantren as Islamic educational institutions that are adaptive, innovative, and capable of contributing to society without losing their Islamic identity. However, the implementation of an integrative curriculum still faces challenges in the form of limited human resources, facilities and infrastructure, teaching materials, and institutional cultural resistance. The conclusion of the study affirms that the integration of religious knowledge and science serves as an important foundation for producing a generation with strong character, broad insight, and the ability to compete at both national and international levels. The implications of this study provide conceptual contributions to the development of pesantren curricula as well as practical recommendations for pesantren administrators in designing Islamic education that is integrative, adaptive, and responsive to global challenges.